Between the «duty to remember» and the political use of forgetfulness: Mexico, Argentina and their recent past (2019)
This article analyses the official memory of the violent and traumatic past during the presidencies of Cristina Fernández de Kirchner in Argentina (2007-2015) and Felipe Calderón in Mexico (2006-2012). In methodological terms, this article adopts one of comparison by contrast, which seeks to shed light on specific characteristics of each particular case and show how said characteristics affect the process. The documental corpus used is composed of presidential speeches and official initiatives in relation to the recent past of these countries. The argument postulates that kirchnerismo kept a policy of a «duty to remember» in line with a political use of the polarising past, and panismo, in the tendency of the «right to forget», synchronised with a political use of the reconciliatory past.